The Effect of Plank Exercise Variations on Arm Muscle Strength in Junior Male Floor Gymnasts Athletes of the FGI Medan in 2025 (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
In floor gymnastics, strength is a key factor in performing movements correctly and achieving the desired results. To perform floor gymnastics movements such as handstands, handsprings and so on, strong arm muscles are needed to support the body. The stronger the gymnast's or athlete's arm muscles, the more flexibility they will have in their lower back, and the better their hand spring skills will be. In this floor gymnastics movement technique, the main problem lies in the strength of the arm, hand, shoulder, abdominal, thigh, and leg muscles, as well as the tightness of each body part. If arm muscle strength is not trained, technical ability in floor gymnastics will not achieve maximum results. This study aims to determine the effect of plank exercise variations on arm muscle strength in junior male floor gymnasts at FGI Medan in 2025. The research method used is a quantitative experimental method. The research design is a one-group pre-test and post-test design. The population in this study consists of 5 athletes. The sampling technique used is total sampling. The sample size used was 5 athletes. The results of the first hypothesis analysis obtained a t-value of 10.06 > t-table 2.132, thus Ha was accepted and Ho was rejected. It can be concluded that there is an effect of plank exercise variations on arm muscle strength in junior male floor gymnasts of the FGI in 2025.